3D printed tensile and flexural prototypes of thermoplastic matrix reinforced with multi-materials: A statistical analysis. (2021) - Kumar, Sudhir; Singh, Rupinder; Singh, T.P.; Batish, Ajay
Abstract: Fused deposition modelling (FDM) is one of the established low cost 3D printing techniques for preparation of functional/ non functional prototypes from thermoplastic composite matrix (prepared as multi/ hybrid blended material). But hitherto little has been reported on multi material reinforced thermoplastic matrix in successive 3D printed layers from repeatability view point. Since the adaptability of any processing technique is dependent upon repeatability/ reproducibility (for which the process output must be statistically controlled), this work reports the statistical analysis of 3D printed tensile and flexural samples printed on FDM as functional prototypes of poly lactic acid (PLA) matrix reinforced with multi materials (poly vinyl chloride (PVC), wood dust and magnetite (Fe3 O4 ) powder) as functionally graded thermoplastic matrix. Further in this work functional prototypes of tensile and flexural sample were 3D printed and tested for their mechanical properties to analyze the process capability index (Cp and Cpk) along with morphological characteristics using optical images of the fractured surfaces. The result of the study suggests that the process was observed to be in statistical control as Cp and Cpk was found to be more than 1 for tensile and flexural properties. Based upon optical photo micrographs it has been ascertained that the optimized 3D printing parameters resulted into uniform morphological features (based upon surface roughness (Ra) and amplitude distribution function (ADF), peak count (PC) and bearing ratio (BR) curve).